Social Capital of Hellen Keller International in the Development of Inclusive Education in East Java - Ucca Arawindha; Slamet Thohari (Indonesian Journal of Disability Studies, 2018)
The problems of disability in Indonesia are crucial, such as problems of stigma, social inequalities, as well as education issues. In addition to the low level of education, disability education has also experienced segregation, in general they are placed in separate education from non-disabled students, ie in special schools (SLB). The existence of SLB is no longer the right choice for people with disabilities. So, today many urgent and seek education that aims to blend disability with others. Including one of the existing institutions in East Java, namely Hellen Keller International. This paper seeks to trace the social capital utilized by the Hellen Keller International (HKI) institution in pursuing inclusive education in East Java. The data search is coupled with descriptive qualitative research method that is using interview, observation, and documentation. The results of this study indicate that HKI has inclusive education development strategy in East Java by utilizing social capital in the form of network and trust. HKI seeks to raise public awareness, especially the local government and related agencies, through public discussions and dialogue. HKI utilizes social networking capital, by bringing in public figures, such as humanists and academics in the process of discussion. It is the first step that makes HKI have confidence in carrying out the development of inclusive education next stage until issuing regulation in the form of Governor Regulation, No, 6, 2011. The conclusion of this research is the utilization of social capital as a strategy undertaken HKI as a non-governmental organization has a significant role in seeking inclusive education in East Java.